If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2h + -7)(2h + -7) = 0 Reorder the terms: (-7 + 2h)(2h + -7) = 0 Reorder the terms: (-7 + 2h)(-7 + 2h) = 0 Multiply (-7 + 2h) * (-7 + 2h) (-7(-7 + 2h) + 2h * (-7 + 2h)) = 0 ((-7 * -7 + 2h * -7) + 2h * (-7 + 2h)) = 0 ((49 + -14h) + 2h * (-7 + 2h)) = 0 (49 + -14h + (-7 * 2h + 2h * 2h)) = 0 (49 + -14h + (-14h + 4h2)) = 0 Combine like terms: -14h + -14h = -28h (49 + -28h + 4h2) = 0 Solving 49 + -28h + 4h2 = 0 Solving for variable 'h'. Factor a trinomial. (7 + -2h)(7 + -2h) = 0Subproblem 1
Set the factor '(7 + -2h)' equal to zero and attempt to solve: Simplifying 7 + -2h = 0 Solving 7 + -2h = 0 Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2h = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2h = 0 + -7 -2h = 0 + -7 Combine like terms: 0 + -7 = -7 -2h = -7 Divide each side by '-2'. h = 3.5 Simplifying h = 3.5Subproblem 2
Set the factor '(7 + -2h)' equal to zero and attempt to solve: Simplifying 7 + -2h = 0 Solving 7 + -2h = 0 Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2h = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2h = 0 + -7 -2h = 0 + -7 Combine like terms: 0 + -7 = -7 -2h = -7 Divide each side by '-2'. h = 3.5 Simplifying h = 3.5Solution
h = {3.5, 3.5}
| 2x+118=2x+68 | | 4x+6(-3)=14 | | 4(-3)+6y=14 | | 4h^2(4h^2)= | | 4u(u+4)=2u+28 | | 25x+1= | | 118/298 | | 3x+9=0o | | d=stfor*s | | 2/3/m-n=12 | | 5w^2+10w-75=0 | | 8b=3b+31 | | 2b^2-c-10=5 | | 7/x-4=3/5 | | 2.2r+0.47=1.78 | | -3x+2-5(7-8x)=4x+3x-(2x+3)+27x | | 121/j-11/1=0 | | A=12bh+12ch | | 5x-45=4x-10 | | 4x-4=62 | | 9y*1-y*0ify=-8 | | X/8-1=2-x/4 | | 20=6y+x | | X+Y-5= | | 6x+8y+18z= | | 9a+28=10a-180 | | 0.6x+17.4=x-1.52 | | h=(2a)/(b) | | 5m^2+2m=4 | | 1-2/4m=mm | | (4p^2-8p-7)+(2p^2+4p+3)= | | h=(2a)/(b);b |